IDENTIFYING THE KEY FACTORS OF POVERTY IN SOUTH BUTON REGENCY - Lestari, Miming (AT TARIIZ : Jurnal Ekonomi dan Bisnis Islam, 2025)
Poverty in South Buton Regency reflects a complex multidimensional challenge, characterized by disparities in access to education, health, infrastructure, and economic opportunities. This study uses a descriptive qualitative approach to identify the main determinants of poverty in the region, by analyzing regional planning documents such as the 2025-2030 PRSP as well as secondary data from BPS and academic literature. The results show that poverty in South Buton is not just a matter of low income, but is closely related to geographical isolation, limited infrastructure, dependence on the informal sector, as well as institutional fragmentation in program implementation. By referring to Amartya Sen's capability approach and Alkire-Foster's multidimensional poverty index, this study emphasizes the importance of contextual, cross-sectoral, and area-based poverty reduction strategies. The findings are expected to strengthen policy planning that is more inclusive, responsive, and effective in achieving the Sustainable Development Goals (SDGs), especially the poverty alleviation target (Goal 1) at the local level.